(untitled) (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Induction of labour in the third trimester of pregnancy may be considered beneficial in many clinical circumstances. Objective: The aim of this study was to find the effectiveness and safety of a novel dosing regimen of oral misoprostol in a Bangladeshi sample. Methods: A cross sectional study was conducted in the Department of Obstetrics and Gynecology, Sir Salimullah Medical College & Mitford Hospital, Dhaka from October 2008 to September 2009 based on the guideline of American College of Obstetricians and Gynecologists. Fifty nine cases were enrolled according to inclusion criteria by clinical pelvimetry and bishop scoring. Contracted pelvis, evidence of cephalopelvic disproportion, placenta previa, unexplained vaginal bleeding, grand multipara, fetal malpresentation, previous uterine scar and fetal distress cases were excluded. Misoprostol was administered per orally. Maternal outcome was assessed by normal vaginal delivery, caesarean section, maternal distress, perineal tear, cervical tear, uterine hyper-stimulation and fetal outcome was assessed in the form of fetal distress, meconium stained amnions, neonatal admission, perinatal death and no complication. Statistical analysis was done using SPSS v 13. Probability value was set at P<0.05 for statistical significance. Results: Mean age was 25.69(5.04) years and mean age of gestation was 38.23(4.3) weeks and 59% were in regular antenatal checkup. Misoprostol was administered orally, 15% single, 37% double, 34% three and l4% were more than three doses. Following induction, 85% had normal vaginal delivery, 10% caesarean section and 5% had forceps delivery. For induction, 56% were due to preeclampsia, eclampsia & other pregnancy induced hypertension, 10% postdated pregnancy, 9% were unfavorable cervix, 7% IUD, l4% elective cases due to medical disorder, 2% had premature rupture of membrane, other causes were 3%. By bishop score assessment 54% had unfavorable and 46% had favorable cervix. In neonate’s outcome, 34% had no complications, 19% meconium stained, 19% neonatal admission, 9% fetal distress and 20% had perinatal death including IUD. In maternal outcome, 69% no complications, 10% perineal tear, 10% caesarean section, 3% maternal distress, 3% cervical tear, 2% uterine hyper-stimulation, 2% episiotomy. There were no significant differences. Conclusions: Stepwise oral misoprostol was well tolerated with no increase in maternal side effects. There was also a trend towards more fetal safety in the oral misoprostol. Perhaps the most significant finding of our study is the lower cesarean section rate in the women who received the oral regimen. J Shaheed Suhrawardy Med Coll, 2014; 6(2):49-52